My monster and me - Hussain, Nadiya (Viking, an Imprint of Penguin Random House, 2021)
"A touching story about a little boy whose worry monster follows him everywhere he goes. It's there when he gets dressed, when he wants to play with his toys, and even when his friends come over to visit. How can he escape his worries?"--